S21.1 Youth and community based research. (14th July 2019) - Flicker, Sarah
Abstract : This paper reports on the micro-, meso-, and macro-level impacts of creating and sharing digital stories created by Indigenous youth leaders about HIV prevention activism in Canada. Eighteen participants created digital stories and hosted screenings in their own communities to foster dialogue. Data for this paper is drawn from individual semi-structured interviews with the youth leaders, audio-recordings of audience reflections, and research team member's field notes collected between 2012–2015 across Canada. Data were coded using NVIVO. A content analysis approach guided analysis. The process of sharing their digital stories had a positive impact on the youth themselves and their communities. Stories also reached policy makers. They challenged conventional public health messaging by situating HIV in the context of Indigenous holistic conceptions of health. The impact(s) of sharing digital stories were felt most strongly by their creators, but rippled out to create waves of change for many touched by them. Participatory visual methodologies can be powerful tools in creating social change and reducing health disparities. Disclosure: No significant relationships.